Genetic diversity analysis of yardlong bean genotypes (Vigna unguiculata subsp. sesquipedalis) based on IRAP marker - Muhammad Habib Widyawan; Sri Wulandary; Taryono (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Widyawan MH, Wulandary S, Taryono. 2020. Genetic diversity analysis of yardlong bean genotypes (Vigna unguiculata subsp. sesquipedalis) based on IRAP marker. Biodiversitas 21: 1101-1107. Inter-Retrotransposon Amplified Polymorphism (IRAP) marker is a PCR-based molecular marker that detects polymorphism between retrotransposon sites. This marker has been utilized and successfully assessed genetic diversity in many crop species. Yardlong bean (Vigna unguiculata subsp. sesquipedalis) was an important vegetable legume crop that grown mainly for its fresh pod that rich in nutritional benefits for humans, ultimately dietary fiber and protein. Trends of people awareness to nutritional content of food are increasing, therefore breeding for quality traits is important. Genetic diversity analysis is an important and elementary step in breeding programs in order to determine the breeding strategy. The aims of this research are to perform an optimization of IRAP marker and applied it for genetic diversity analysis in 16 yardlong bean genotypes. Seven primers were used as marker in a pair or single combination and resulted in 11 optimized markers that able to be used for genetic diversity analysis. Sixteen yardlong bean genotypes consisting of commercial cultivars and local genotypes from Indonesia were genotyped using eleven IRAP markers. Marker polymorphism and diversity parameters from each marker i.e. Percentage of Polymorphic Loci (PPL), Expected Heterozygosity (He), Polymorphic Information Content (PIC), Effective Multiplex Ratio (EMR), Marker Index (MI), Discriminating Power (D), and Resolving Power (RP) were calculated. Based on those values, several markers used in this study were considered as informative and efficient in terms of analyzing genetic diversity in yardlong bean. Jaccard's method was used to measure genetic similarity and it is revealed that there is high level of similarity between yardlong bean genotypes used in this study. Thus, it is implied that there is a narrow genetic diversity of yardlong bean genotypes used in this study. Cluster analysis was performed to construct dendrogram based on genetic similarity and classified 16 yardlong genotypes into 4 clusters. Interestingly, majority of the clusters formed were not able to classified genotypes based on their origin. The result of cluster analysis then confirmed by Principal Coordinate Analysis (PCoA) that able to explain 47.76 % of total variation. The results of this study provide a foundation for the genetic diversity analysis based on IRAP marker and genetic improvement in yardlong bean.